EFFECT OF ULTRASONICATION IN THE DEVELOPMENT OF THIN FILM COMPOSITE MEMBRANES FOR FORWARD OSMOSIS APPLICATIONS - Tjandra, Jeremiah
Forward Osmosis (FO) is a process that can be an alternative solution in water treatment. However, FO still has several challenges which besides being caused by external factors, can also be caused by the membrane structure. The active layer of the FO membrane usually uses polyamide (PA) material, while the support layer usually uses polysulfone (PSf) material. Although PSf tends to have high selectivity, it is less resistant to organic solvents and high temperatures. To overcome this, polypropylene (PP) can be an alternative material. However, PP is hydrophobic which can reduce water flux and inhibit active layer fabrication. Therefore, it is necessary to modify the hydrophilicity of the PP membrane. Improvement on the active layer side can also be done with the Ultrasonic Assisted Interfacial Polymerization (UAIP) method. UAIP uses ultrasonic waves to improve membrane performance by making nanobubbles that can help the interfacial polymerization process. This research will focus on the method of fabricating Thin Film Composite hollow fiber membranes based on PP and PA materials which is carried out in 2 stages, namely modification of the hydrophilicity of PP and fabrication of PA with UAIP. There are 2 methods of modifying the hydrophilicity of PP, namely swelling and acid dipping. Meanwhile, in the UAIP process, there are 3 stages that will be carried out, namely the initial one factor at time experiment, the 25-1 factorial experiment, and the evaluation experiment of the effect of ultrasonic on the performance of the FO membrane. The membrane will be characterized and evaluated by looking at its functional groups, hydrophilicity, and its performance, both water flux and selectivity. Factors to be examined in the UAIP process include reactant concentrations, curing methods, time for each treatment, and ultrasonication treatment. Based on the analysis results, the best pre-treatment method is the swelling method using IPA as the permeator. This method can produce a fairly hydrophilic and homogeneous PP support layer with good flux and selectivity compared to other methods. In addition, the results of the analysis also show that the ultrasonic effect is statistically proven to have a significant effect on both the water flux and selectivity models with a significance level of up to 99%. Ultrasonic can increase the performance of membranes up to 14% to 1.8 LMH for water flux and 26% to 3.65 for water and salt selectivity.